Atribuição Inequívoca dos Sinais de RMN de 1H e de 13C do Glaucolídeo B, Síntese de seus Derivados e Síntese de 2-Fenil-6,7-exo-Isopropilidenodioxi- 8-Oxabiciclo-[3.2.1]-Oct-2-eno, Visando a Obtenção de Novos Herbicidas - Adilson Vidal Costa (2008)
Considering the increasing need of new chemical products for therational and efficient weeds control, it was conducted a research of newcompounds provided with herbicide activity, as well as the study for unequivocal determination of Glaucolide B [1], structure a sesquiterpene lactone containing a cycle of ten members. For this, the Glaucolide B was isolated from the aerial part of Vernonia fruticulosa Mart., from Asteraceae family. The catalytic hidrogenation of compound 1 resulted in the compound 2 with 74% yield and in the compound 3 with 25% yield. The treatment of compounds 1, 2 and 3 with water and trifluoracetic acid led to the compounds 6, 5 and 4, with 68%, 76% and 65% yields, respectively. Compound 7 was obtained by the deoxygenation of compound 2 with 26% yield.In the present work the 2-phenyl-6, 7-exo-isopropylidenedioxy-8-oxabicyclo[3.2.1]oct-2-ene [27] with potential herbicide activity, not yetdescribed in the literature, was also synthesized. Initially this compound was prepared from cycloaddition [3+4] between the furan and oxyallyl cation generated by the treatment 1-bromo-1-phenylpropan-2-one [22] with ethylamine, leading to the obtaining of the -phenyl-8-oxabicyclo[3.2.1]oct-6-en- 3-one [23]. Compound [23] was converted on a two stages process in 2-phenyl- 6,7-exo-isopropylidenodioxy-8-oxabicyclo[3.2.1]octan-3-one [25]. Treatment of this compound with sodium borohydride, followed by alcohol dehydratation led to the alkene.The compounds studied had their structures determined byspectroscopic methods: infrared and nuclear magnetic resonance, including COSY, HMQC, DEPT and NOESY techniques. For Glaucolide B spectra were obtained varying the temperature from -43ºC to 27ºC, with intervals of 10ºC.The evaluation of the activity of those products was made in preliminarybioassays, using, as test plants, the species Physalis ixocarpa, Loliummultiflorum, Trifolium alexandrinum and Amaranthus hypochondriacus, being applied doses of 50, 100 and 200 mM of the synthesized compounds. The main products with herbicide activity were the compounds 4 and 5, which caused higher effect on all tested plants, standing out the inhibition of 90% caused by compound 5 on the germination of P. ixocarpa seeds. Evaluation of the oxabicyclos 27 and 34 was made under laboratory conditions with plants of Sorghum bicolor L. and Cucumis sativus L. using doses of 100 mM and 250 mM. In these bioassays, the isomeric compound 27 revealed to be most active uponthe development of the root system of the tested plants. These results indicated that the evaluated compounds are a class of organic compounds having a potential herbicide activity, thus justifying more detailed studies.